The lived experience of depression and coping : perspectives of depressed males and their spouses/significant others - Witte, Jill (My University, 2009)
The purpose of this study was to explore and describe the lived experiences of depression and coping from the perspectives of men and their spouses/significant others. Depression affects over 6% of Americans. More than 80% of patients with depressive disorders are estimated to seek care from primary care providers. Despite numerous studies on depression, effects of depression and treatment issues, there is paucity of research related to males with depression. To enhance the health care provider's understanding, the following research questions were asked: (a) What is the lived experience of depression in men and their spouses/significant others? (b) How does the family cope with the recurrence of depression? and (c) How can the advanced practice nurse (APN) help with depression? Parse's (1998) Human Becoming Theory provided the framework for this study. A phenomenological qualitative design was used to gather narrative data in order to explore and describe their experiences. Open-ended interviews with both the depressed man and his spouse/significant other took place jointly. Data were analyzed according to Giorgi's (1995) approach. The sample comprised a convenience sample of six men diagnosed with major depressive disorder (MOD) and their significant other/spouse. The settings for data collection were private psychiatric clinics, depression support groups and community centers. The researcher was the data collection instrument. Interviews were audiotaped and transcribed verbatim. Data were analyzed according to Giorgi's (1995) approach. Data analysis of the depressed men's perspectives indicated three main themes: (a) Diagnosis: What is it? (b) Coping: Pulling Through; and (c) The Treatment: Relief. Data analysis of spouses/significant others indicated three main themes: (a) Disbelief: What now? (b) Continuing On: Wishing for Normalcy; and (c) The Treatment: Relief. Nurse practitioners can utilize the findings of this study to optimize the care they give to the depressed male and his spouse/significant other. This study showed that a more comprehensive nursing evaluation of the male's depression and its effects on the spouse/significant other would help identify areas to focus treatment. Through interventions tailored to meet the patient and spouse's/significant other's needs, APNs can have a more profound and lasting impact on the outcomes of the patient and spouse/significant other.
A Clinical Paper Submitted in Partial Fulfillment of the Requirements for the Degree of Master of Science - Nursing - Family Nurse Practitioner --University of Wisconsin-Oshkosh, 2008
Keywords: Adaptation (Psychological); Depression in men; Men's Mental health; Depression, Mental